Assessment of changes in population ageing in regions of the V4 countries with application of multidimensional scaling - Dehnel, Grażyna; Gołata, Elżbieta; Walesiak, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
The study investigates the variation in population ageing in four Visegrad countries (V4) and across their NUTS2 regions in 2016 compared to 2005. Population ageing was assessed using the median age, old-age rate, double ageing index, ageing index, and old-age dependency ratio. The authors took into account causes that explain changes occurring at the bottom and at the top of the population pyramid. By applying multidimensional scaling combined with the composite indicator and the Theil decomposition, the study identified differences in the level of population ageing in a two-dimensional space and the dynamics of these changes. Such an approach, with the visualization of the results, enriches this interpretation. In the reference period the process of population ageing in the V4 countries and their regions accelerated considerably. The disproportion between regions has increased in Slovakia, slightly increased in Poland, and decreased in the Czech Republic and Hungary
Argumenta Oeconomica, 2020, Nr 1 (44), s. 77-100